PENGGUNAAN OBAT SITOSTATIKA PADA ANAK-ANAK YANG MELAKUKAN KEMOTERAPI DI RSUP Dr. SARDJITO YOGYAKARTA TAHUN 2010 - Maria Wisnu Donowati; Ayu Y.N. Pramodhawardani; Ika Lestari (Universitas Sanata Dharma, 2016)
Abstract: Approximately 11.000 new child cancer cases per annum. An appropriate cytostatic drug regimen can worse renal function. Aims of this research to determine the use of cytotoxic in children chemotherapy based on GFR according Schwartz and CB formulas in RSUP Dr. Sardjito Yogyakarta 2010 period. Cytotoxic drugs include antibiotic and non antibiotic cytotoxics. An observational descriptive evaluative study with retrospective design was done. Inclusion criteria were patient 0 - 12 years with creatinine serum data and exclusion criteria were acute or chronic kidney failure with creatinine serum >5 mg/dL. The data taken were patient's age, height, weight, and creatinine serum. Adjustment doses was evaluated based on 2 GFR <60 mL/min/1.73 m for cytotoxic drugs. Dose adjustment was evaluated according to DIH and BSA guidelines. Using 171 patient's datas with 160 cases of antibiotics prescription and 704 cases of non antibiotics prescription. 1,8%; 5,6% cases of antibiotics prescription and 1,0%; 3,6% cases of non antibiotics prescription required adjusment doses according to the Schwartz and CB formulas. Unappropriate doses were found for doxorubicine and bleomycine as cytotoxic antibiotics usage and etoposide, L-asparginase, dan cyclophosphamid as non cytotoxic antibiotics usage. Keywords : cytotoxic drugs, children, glomerular filtration rate, Schwartz formula, CounahanBarratt formula.